High‐Efficiency E‐Beam Pumped Deep‐Ultraviolet Surface Emitter Based on AlGaN Ultra‐Thin Staggered Quantum Wells. Issue 18 (25th June 2022) - Wang, Yixin; Yuan, Ye; Tao, Renchun; Liu, Shangfeng; Wang, Tao; Sheng, Shanshan; Quach, Patrick; CM, Manoj Kumar; Chen, Zhaoying; Liu, Fang; Rong, Xin; Jin, Peng; et al.
Abstract: A 2‐inch wafer‐scale electron‐beam (e‐beam) pumped deep‐ultraviolet surface emitter (DUVSE) with high efficiency and high output power at an emission wavelength of 248 nm is reported. This DUVSE benefits from ultra‐thin staggered AlN/AlGaN/GaN multiple quantum wells (MQWs), which compromise the electron–hole overlap and carrier confinement and thus significantly improve the emission efficiency. The wall‐plug‐efficiency (WPE) is increased by six times to 5.25% in comparison to that of conventional DUV light‐emitting devices (LEDs) based on AlGaN MQWs. This WPE is achieved under an anode voltage and current of 8 kV and 1 mA, where the output power is 420 mW. This output power can be further enhanced to 702 mW by increasing the anode current to 3 mA. The enhanced WPE and uniform electron beam distribution lighten the avenue to achieve a wafer‐scale high power dense DUV light source, which is a challenge for conventional DUV‐LEDs, in particular with an emission wavelength of less than 250 nm. Abstract : By benefitting from an ultra‐thin staggered quantum wells structure, a 2‐inch wafer‐scale e‐beam pumped deep‐ultraviolet surface emitter (DUVSE) is achieved, with excellent wall‐plug‐efficiency as high as 5.2% at an emission wavelength of 248 nm. This achievement displays the prospective for high‐efficiency DUVSE in water/air purification, disinfection, medical treatment, and so on.